A Study On The Market Efficiency of Chinese Stock Market - Qi, Yubing (2010)
The main purpose of this dissertation is to test whether the Chinese stock market is weak-form efficient. To solve this problem, the Random Walk Theory is tested. To be more specific, the randomness of the Chinese stock market is tested in two different aspects: one aspect is the tests for unit root, which are to detect the patterns of the trend in the time series; the other is tests for serial correlation, which are to detect the dependence of different observations in the time series. The unit root is tested by the Dickey-Fuller test, Augmented Dickey-Fuller test and Phillips-Perron test, on the other hand, the serial correlation is tested by the run test, Box-Pierce Q-statistic test and Ljung-Box Q*-statistic test. Moreover, the nonlinear dependence of the stock return series is also tested by the DBS test and the ARCH effects by the ARCH-LM test. The results of the tests indicate that the Chinese stock market does not follow the randomness; hence, the Chinese stock market is not weak-form efficient. Furthermore, the estimation of the GARCH (1, 1) model shows that the return series for the SSE and SZSE can be modelled by this model. Overall, the conclusion of this study is that the Chinese stock market is not weak-form efficient.